PERAN GURU PAI DALAM MENCEGAH PAHAM RADIKALISME BAGI SISWA DI MTS IRSYADUL ANAM KIYUDAN SELOMARTANI KALASAN SLEMAN YOGYAKARTA - Saprialman Saprialman; Ferianto Ferianto; Yuli Salis Hijriyani; Khairil Aswan (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2022)
This research departs from the phenomenon of radicalism that occurs in society, especially in the world of education. The understanding of radicalism is an understanding that must be immediately overcome and avoided from students because it is contrary to the Islamic religion which is rahmatan lil 'alamin and not in accordance with the purpose of organizing Islamic education itself. The focus of the problem in this study is "the role of Islamic Religious Education teachers in preventing radicalism for students". This research is a qualitative research with a descriptive-qualitative type of research. The subjects of his research were PAI teachers, principals and caregivers of Irsyadul Anam Islamic boarding schools as well as advisors at MTs Irsyadul Anam. Data analysis was carried out with interactive models from Miles and Huberman, namely, data condensation, display data, and conclusion drawing/verifications. The results showed that the role of PAI teachers in preventing radicalism for students at MTs Irsyadul Anam Kiyudan Selomartani Kalasan Sleman Yogyakarta can be seen from three aspects, namely: (1) Delivery of Islamic Learning Materials. (2) Application of Learning Methods, and (3) Assistance in Extracurricular Activities.